Handicaps in using English faced by students of accounting department, State Polytechnic of Malang - Sigit Budisantoso (UPT P2M Politeknik Negeri Malang, 2011)
Practicing English is always a big problem to many students in Accounting Department, State Polytechnic of Malang. They have their own reasons not to be confident. A learner will certainly get a loss if he/ she cannot speak the targeted language because a language is learnt to be used as a communication means. In general, a learner will not be confident to practice his/ her English because of the following reasons. First, they are afraid of making grammatical mistakes. It is right that Indonesian grammar derives from English grammar. But Indonesian grammar does not have some aspects that are used by English grammar, such as tenses, plurality, different prepositions, and different pronouns. Second, they are afraid of making wrong pronunciation. English words are pronounced differently. Many of the respondents are not confident to pronounce English words. Third, they always feel that they are lack of vocabulary. The explanation of this problem is simple. They feel lack of English words because they do not like reading English books, English magazines, or any other English works. Forth, the people around them do not support them. In other words, they are afraid of practicing their English because the people around them are always mocking on them when they are practicing their English. In conclusion, learners have their own reasons why they are not confident to practice their English. That is why an English teacher is always demanded to create a suitable teaching strategy for his classrooms so that most of his/ her students are confident to practice their English.